Synthesis of (−)-halichonic acid and (−)-halichonic acid B - Reber, Keith P.; Niner, Emma L. (Beilstein Journal of Organic Chemistry, 2022)
The first syntheses of the amino acids (–)-halichonic acid and (–)-halichonic acid B have been achieved in ten steps starting from commercially available (−)-α-bisabolol. The optimized synthetic route includes a new purification method for isolating (−)-7-amino-7,8-dihydrobisabolene in enantiomerically pure form via recrystallization of its benzamide derivative. The key intramolecular aza-Prins reaction forms the characteristic 3-azabicyclo[3.3.1]nonane ring system of halichonic acid along with the lactonized form of halichonic acid B in an 8:1 ratio. Optical rotation measurements confirmed that these synthetic compounds were in fact the enantiomers of the natural products, establishing both the relative and absolute configurations of the halichonic acids.
Keywords: alkaloid; amino acid; aza-Prins reaction; cascade reaction; natural product

(untitled) - Mehbub, M. F.; Lei, J.; Franco, C.; Zhang, W. (Mar. Drugs, 2014)

(untitled) - Abdelaleem, E. R.; Samy, M. N.; Desoukey, S. Y.; Liu, M.; Quinn, R. J.; Abdelmohsen, U. R. (RSC Adv., 2020)

(untitled) - Shady, N. H.; El-Hossary, E. M.; Fouad, M. A.; Gulder, T. A. M.; Kamel, M. S.; Abdelmohsen, U. R. (Molecules, 2017)

(untitled) - Raiju, K.; Hitora, Y.; Kato, H.; Ise, Y.; Angkouw, E. D.; Mangindaan, R. E. P.; Tsukamoto, S. (Tetrahedron Lett., 2019)

(untitled) - Hitora, Y.; Ogura, K.; El-Desoky, A. H. H.; Ise, Y.; Angkouw, E. D.; Mangindaan, R. E. P.; Tsukamoto, S. (Chem. Pharm. Bull., 2021)

The Alkaloids - Bick, I. R. C.; Hai, M. H. (Aristotelia Alkaloids, 1985)

(untitled) - Gujarati, P. D.; Reber, K. P. (Synthesis, 2022)

(untitled) - Argade, M. D.; Straub, C. J.; Rusali, L. E.; Santarsiero, B. D.; Riley, A. P. (Org. Lett., 2021)

(untitled) - Pronin, S. V.; Reiher, C. A.; Shenvi, R. A. (Nature, 2013)

(untitled) - Kitagawa, I.; Yoshioka, N.; Kamba, C.; Yoshikawa, M.; Hamamoto, Y. (Chem. Pharm. Bull., 1987)

(untitled) - Clerici, F.; Gelmi, M. L.; Gambini, A.; Nava, D. (Tetrahedron, 2001)

(untitled) - Brummond, K. M.; Painter, T. O.; Probst, D. A.; Mitasev, B. (Org. Lett., 2007)

(untitled) - Szostak, M.; Spain, M.; Eberhart, A. J.; Procter, D. J. (J. Am. Chem. Soc., 2014)

(untitled) - Pelletier, G.; Bechara, W. S.; Charette, A. B. (J. Am. Chem. Soc., 2010)

(untitled) - Mai, T. T.; Viswambharan, B.; Gori, D.; Kouklovsky, C.; Alezra, V. (J. Org. Chem., 2012)

(untitled) - Mahrwald, R.; Quint, S. (Tetrahedron Lett., 2001)

Sodium Dihydrido-Bis(2-methoxyethoxo)-Aluminate (SDMA): A Versatile Organometallic Hydride - Strouf, O.; Casensky, B.; Kubanek, V. (Elsevier, 1985)

(untitled) - Nicolaou, K. C.; Mathison, C. J. N.; Montagnon, T. (Angew. Chem., Int. Ed., 2003)

(untitled) - Sullivan, B. W.; Faulkner, D. J.; Okamoto, K. T.; Chen, M. H. M.; Clardy, J. (J. Org. Chem., 1986)

(untitled) - Bensemhoun, J.; Bombarda, I.; Aknin, M.; Vacelet, J.; Gaydou, E. M. (Biochem. Syst. Ecol., 2008)

(untitled) - Jamison, M. T.; Macho, J.; Molinski, T. F. (Bioorg. Med. Chem. Lett., 2016)

(untitled) - Abdjul, D. B.; Kanno, S.-i.; Yamazaki, H.; Ukai, K.; Namikoshi, M. (Bioorg. Med. Chem. Lett., 2016)

(untitled) - Kochi, T.; Ellman, J. A. (J. Am. Chem. Soc., 2004)

(untitled) - Ota, K.; Hamamoto, Y.; Eda, W.; Tamura, K.; Sawada, A.; Hoshino, A.; Mitome, H.; Kamaike, K.; Miyaoka, H. (J. Nat. Prod., 2016)

(untitled) - Ichikawa, Y. (Chem. Lett., 1990)